First season MWA EoR power spectrum results at redshift 7 - Beardsley, A.; Hazelton, B.; Sullivan, I.; Carroll, P.; Barry, N.; Rahimi, M.; Pindor, B.; Trott, Cathryn; Line, J.; Jacobs, D.; Morales, M.; Pober, J.; et al. (Institute of Physics Publishing, 2016)
The Murchison Widefield Array (MWA) has collected hundreds of hours of Epoch of Reionization (EoR) data and now faces the challenge of overcoming foreground and systematic contamination to reduce the data to a cosmological measurement. We introduce several novel analysis techniques, such as cable reflection calibration, hyper-resolution gridding kernels, diffuse foreground model subtraction, and quality control methods. Each change to the analysis pipeline is tested against a two-dimensional power spectrum figure of merit to demonstrate improvement. We incorporate the new techniques into a deep integration of 32 hours of MWA data. This data set is used to place a systematic-limited upper limit on the cosmological power spectrum of ∆2 ≤ 2.7×104 mK2 at k =0.27 h Mpc-1 and z = 7.1, consistent with other published limits, and a modest improvement (factor of 1.4) over previous MWA results. From this deep analysis, we have identified a list of improvements to be made to our EoR data analysis strategies. These improvements will be implemented in the future and detailed in upcoming publications.